High power single-sided Bragg reflection waveguide lasers with dual-lobed far field - Wang, L. J. (2013)
We report on 980-nm InGaAs/GaAs lasers with dual-lobed far field based on a single-sided Bragg reflection waveguide (BRW). The high slope efficiency ∼0.92 W/A and a continuous wave (CW) output power >1.5 W (3.2 W pulsed) have been obtained. The threshold current density is as low as 253 A/cm2 for a 1.5-mm-long device and the transparency current density is only 140 A/cm2. The further analysis shows the intrinsic reason for the single-lobed or the dual-lobed far-field distribution is determined by the mode shape in the cavity, not the single-sided or dual-sided BRW structure. The condition to achieve a narrow single-lobed far-field distribution is discussed.